A morphometric study of the brain ventricles of patients diagnosed with Chronic Hydrocephalus at Groote Schuur Hospital - Lichaba, Reagobaka (Department of Human Biology, 2025)
Hydrocephalus (HCP) is a cerebrospinal fluid condition of the central nervous system, which when it accumulates causes an increase in ventricular enlargement and raised intracranial pressure (ICP). Raised intracranial pressure in a fixed volume space is dangerous as it presses onto the brain parenchyma and the surrounding areas and may damage them. Ventricular enlargement is a radiological indicator of hydrocephalus and has been one of the features used to diagnose the condition, with the ICP measurement used to confirm the condition. However, measuring ICP is invasive and puts the brain at risk of bleeding and infections, making it necessary to use non-invasive methods of confirming the condition. This study aims to investigate the clinical features observed on the brain scans of patients with hydrocephalus and seeks to describe the unique shape of the frontal horns and use this shape as a noninvasive diagnostic marker. The study observed the brain magnetic resonance imaging and computed tomography scans of 150 patients who were suspected or known to have hydrocephalus from the Radiology Department at Groote Schuur Hospital. These scans were then divided into three groups, namely, the controls, and chronic and acute hydrocephalus groups. The clinical features commonly observed on the brain scans of patients with hydrocephalus were evaluated, their measurements taken, and their shapes recorded. These features were the Evans Index, temporal horn width, third ventricle width and shape, callosal angle, frontal horn shape, Sylvian fissure width and periventricular white matter changes. This morphometric data was then analysed to determine their relationship with hydrocephalus. Of the clinical features, the frontal horn shape has not been described in the literature. Therefore, it was described in this study, and its association with the measurement of ICP was assessed. There was a statistically significant difference in the morphometric data between the control and chronic HCP groups. In contrast, the difference in the data between the chronic and acute HCP groups was not statistically significant. In all three groups, there was a difference in size between the left and right sides, the right side had smaller measurements than the left. There was a significant difference in frontal horn shape between the chronic and acute HCP groups. Additionally, it was evident that there was a relationship between a specific shape of the frontal horn and the measurement of ICP. The morphometric data of the clinical features were consistent with the literature, except for the Sylvian fissure width. The data in this study showed that the accumulation of CSF occurred mostly on the left side in the clinical features that compared the sides, perhaps suggesting that the condition favoured the left side. The frontal horn shape was different in the chronic and acute HCP groups, it was described as quadrilateral and round, where the quadrilateral shape correlated with the low-moderate ICP, and the round shape correlated with the high ICP reading. Therefore, the frontal horn shape has the potential to be used in the clinical space as a non-invasive imaging marker when differentiating between chronic and acute HCP patients.